Domestic violence challenge and COVID-19 pandemic - Marzieh Nojomi; Ebrahim Babaee (SAGE Publishing, 2020)
By the emergence of the COVID-19 transfers and relocation of people to prevent the spread of infection have been restricted. Long term staying at home during an epidemic increases the probability of interpersonal friction and conflict. During this time, the family members get close together and interactions between family members may be increased. Restricting people's movements during an epidemic can lead to psychological consequences such as stress, anxiety, and domestic violence consequently. The World Health Organization (WHO) emphasis that with the onset of the COVID-19 pandemic, anxiety, and stress have increased worldwide notably.